Royal Society of Medicine Surgical Innovation Day Adrian Tanner Prize Winner 2019: Multidisciplinary care and surgical innovation for the benefit of the patient with head and neck cancer of unknown primary. Issue 7 (July 2020) - Mistry, Rakesh; Walker, Abigail; Walker, Nathan; Ofo, Enyinnaya
Head and neck carcinoma of unknown primary accounts for approximately 1–5% of all head and neck cancers and presents a genuine diagnostic and therapeutic dilemma. Despite advanced investigations, the primary tumour location remains unknown in up to 40% of these cases. Transoral robotic surgery presents a viable diagnostic and therapeutic option in these patients. This surgical innovation alongside advances in the understanding of head and neck cancer biology means that a multidisciplinary approach in the management of these complex patients is of utmost importance to ensure optimal therapeutic outcomes.